Measurement error consequences, applications and solutions - Binner, Jane M., 1961-; Edgerton, David.; Elger, Thomas. (Advances in econometrics, 2009)
The conference, 'Measurement Error: Econometrics and Practice' was recently hosted by Aston University and organised jointly by researchers from Aston University and Lund University to highlight the enormous problems caused by measurement error in Economic and Financial data which often go largely unnoticed. Thanks to the sponsorship from Eurostat, a number of distinguished researchers were invited to present keynote lectures. Professor Arnold Zellner from University of Chicago shared his knowledge on measurement error in general; Professor William Barnett from the University of Kansas gave a lecture on implications of measurement error on monetary policy, whilst Dennis Fixler shared his knowledge on how statistical agencies deal with measurement errors. This volume is the result of the selection of high-quality papers presented at the conference and is designed to draw attention to the enormous problem in econometrics of measurement error in data provided by the worlds leading statistical agencies; highlighting consequences of data error and offering solutions to deal with such problems. This volume should appeal to economists, financial analysts and practitioners interested in studying and solving economic problems and building econometric models in everyday operations.